Efektifitas Penambahan Tepung Daun Pepaya Pada Pakan Terhadap Persentase Karkas Bagian Dada dan Paha Itik Manila: Efektifitas Penambahan Tepung Daun Pepaya Pada Pakan Terhadap Persentase Karkas Bagian Dada dan Paha Itik Manila - Hilmi, Ihsan; Kholis, Nur; Hartati, Hartati; Jubaedah, Siti (Jurnal Ilmiah Ilmu-Ilmu Peternakan, 2024)
Background:  One of the problems that Manila duck farmers often face today is the high price of feed and unstable growth rates. This causes the body weight growth of Manila ducks to not be optimal and has an impact on the percentage of carcasses that are not as expected. Papaya leaves are one type of waste from agricultural businesses that can be used as additional feed by turning them into flour mixed into feed. Papaya leaf flour contains protein, calcium, and phosphorus and can increase the carcass productivity of Manila ducks. Purpose:  This study aims to determine the effect of the addition of papaya leaf flour in feed on the carcass percentage of the chest and thighs of Manila ducks.  Methods: This study used 40 manila ducks aged 6 weeks as material. The method used was a completely randomized design (CRD) consisting of 4 treatments and 5 replications. The treatment consisted of the addition of papaya leaf flour (PO 0%, P1 3%, P2 5%, and P3 7%). Results: The results showed that the addition of papaya leaf flour in feed had a very significant effect (P <0.01) on the percentage of carcasses of the breast and thighs of manila ducks. Conclusion:  From the results of this study, it can be concluded that the addition of papaya leaf flour in feed up to 5% level can increase the percentage of carcasses of breast and thigh of manila ducks.